TIME IS MUSCLE: MANAGEMENT OF CHEST PAIN IN THE EMERGENCY DEPARTMENT. Issue 12 (18th November 2016) - Qureshi, B; Llewelyn, M; Freer, J; Baptiste, P; Harris, T
Abstract : Objectives & Background: Many chest pain assessment protocols include delayed troponin assays, which makes assessment within the Emergency Department (ED) 4-hour UK national target difficult, and increases pressure on medical admissions. Our objective was to evaluate the effect of point-of-care (POC) troponin testing on successful risk-stratification of patients presenting with chest pain. Methods: An audit in a district general hospital ED in London, in two phases: 14th April 2013–15th June 2013; and 15th April 2014–15th June 2014. Between the 2 phases, laboratory-based testing (Roche Cobas E602 multi-channel analyser; limit of detection 5 ng/L and a 99th percentile of 14 ng/L) was replaced by POC troponin (Radiometer ATQ90 analyser; limit of detection 10 ng/L and a 99th percentile of 23 ng/L). A new chest pain protocol was also introduced, with 3 categories: Red for ST-Elevation MIs; Amber for patients requiring inpatient assessment; and Green for low-risk management as an outpatient. In 2013, a non-random sample of patients with chest pain as a presenting complaint was identified from the case notes; in 2014 a non-random sample was extracted from the point-of-care machines. Results: In 2013, data were obtained for 194 patients, and 171 in 2014. In the initial audit, using a lab-based troponin assay, 72.7% (n=141) of patients were managed on the Amber pathway, which reduced to 14.62% (n=25) post introduction of the POC troponin assay (p=0.02). In the initial audit, 23.2% patients (n=45) were managed on the Green pathway and discharged from the ED, compared to 83.04% (n=142) post introduction of POC troponin assay (p<0.001). The proportion of patients correctly put on the Green pathway increased from 91.1% (n=41) to 99.3% (n=41) post introduction of POC assay (p=0.003). The proportion of Amber patients with a troponin measured on arrival increased from 39.7% (n=56) to 100% (n=25; p<0.001). On the green pathway, troponin on arrival had increased from 31.1% (n=14) to 72.5% (n=124; p<0.001). Conclusion: Point-of-care troponin testing was associated with a higher proportion of patients discharged from the ED and managed as outpatients. This most likely resulted from reduced waiting times for the troponin assay, reducing admissions to await these results. This may also explain the association between the introduction of POC troponin assays and a higher proportion of patients correctly assigned to the cardiac assessment pathways.